Breast fibroadenomas in adolescents: current perspectives - Lee M; Soltanian HT (Dove Medical Press, 2015)
Michelle Lee, Hooman T SoltanianDepartment of Plastic and Reconstructive Surgery, University Hospitals Case Medical Center, Case Western Reserve University, Cleveland, OH, USAAbstract: Fibroadenomas are one of the most common benign tumors of the breast in the adolescent population. They account for 68% of all breast masses and 44%–94% of all biopsied breast lesions. Fibroadenomas can range from asymptomatic masses to painful and rapidly growing tumors that can cause significant esthetic distortions of the breast. Given the prevalence of fibroadenomas in the adolescent population and the psychosocial morbidity of finding a mass in the adolescent breast, it is imperative for physicians treating adolescent patients to be familiar and up to date with this disease process. The goal of this article is to provide a brief review of the classification, etiology, symptoms, initial work-up, and update on the management of breast fibroadenomas in the adolescent population.Keywords: breast mass, benign breast neoplasm, breast growth, breast development, breast asymmetry